PENERAPAN MEDIA VIDEO LAGU DAN ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III PADA MATA PELAJARAN IPAS TENTANG DI SDN SIWALANKERTO II SURABAYA - Fairuzzia Nabila; Muhammad Thamrin Hidayat; Asmaul Lutfauziah; Muslimin Ibrahim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low student learning outcomes in science and science subjects are one of the problems faced in Class III B SDN Siwalankerto II Surabaya, this is due to the lack of variety of learning media used by several teachers. Based on the problems above, teachers need to vary the learning media. There are many learning media that can be used by teachers, for example snakes and ladders, smart boards, flashcards, song media. With this, researchers want to apply song video and animation media which aims to determine the increase in student learning outcomes in science subjects. The research method used is quantitative with a one-group pretest-posttest design. The sample for this research was determined from the results of simple random sampling, namely Class III B students, totaling 27 students. Data collection was carried out through observations of learning implementation, learning outcomes tests (pretest and posttest), as well as questionnaires to determine student responses to animated song video media. The learning was carried out in 2 meetings with the results: (1) The results of observations of the implementation of the learning showed that the first meeting was 100% implemented and the second meeting was 100% implemented; (2) Student learning outcomes increased significantly with an average N-Gain score of 0.7258; (3) Student responses to song video and animation media are in the very high category. Thus, it can be concluded that the application of song video and animation media can improve student learning outcomes in science subjects.